The Mediating Role of Knowledge Sharing in the Relationship between Organizational Culture and Teacher Performance at State Islamic Elementary Schools in Buol Regency - Aurannisa, Novi; Abidin, Munirul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to analyze the effect of organizational culture on teacher performance by examining the mediating role of knowledge sharing. The research was conducted using a quantitative approach with a correlational design. Data were collected from 31 teachers at Madrasah Ibtidaiyah Negeri in Buol Regency using a structured questionnaire developed based on established theories. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4. The results showed that organizational culture has a significant direct effect on teacher performance and on knowledge sharing. However, knowledge sharing was found to have no significant direct effect on teacher performance and did not mediate the relationship between organizational culture and teacher performance. These findings suggest that while organizational culture plays a crucial role in shaping teacher performance, knowledge sharing alone is insufficient as a mediating factor. The study contributes to the literature on educational management, particularly within the context of Islamic educational institutions, and highlights the need for further exploration of other potential mediators.